Development and Validation of Digital Literacy Scale for Prospective EFL Teachers - Natalia Christiani; Novalita Fransisca Tungka; Romauli Nainggolan (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
Teacher’s digital literacy competence is crucially important in education nowadays, and a number of scholars have measured the quality of teacher’s digital literacy skills. The available instruments have been developed to assess digital literacy skills of adolescents and graduate school students, while digital literacy skills of prospective teachers have received little attention. This study aimed at developing and validating an instrument to measure digital literacy skills particular to prospective Indonesian EFL teachers. To this end, this study piloted a theoretical model based on a review of the related literature, interviews with Indonesian EFL learners majoring in English Language Education Department and EFL lecturers in East Java, North Sumatera, Central Sulawesi, West Kalimantan, West Papua, East Nusa Tenggara, and Bali. Later, the results were used to verify and develop the digital literacy scale. After developing the scale and administering it to 336 Indonesian EFL learners from seven cities in Indonesia, the researchers validated the scale through both exploratory and confirmatory factor analyses. This study exposes a comprehensive picture of prospective teachers’ digital literacy skills in EFL contexts in terms of eight factors: creative skill, technological skill, personal security skill, internet safety skill, problem-solving skill, informational skill, and communication or netiquette skill. This scale is a valid and reliable tool, and will be useful as an instrument on EFL teachers’ digital literacy skills. The final form of this scale can inform policy development, curriculum design, and training initiatives for prospective EFL teachers targeting digital literacy competence.